Changes in birthweights and perinatal mortality rate in a rural block in South India over 30 years - Anne George Cherian; Jackwin Sam Paul; Vinod Joseph Abraham; Venkata Raghava Mohan; Jasmin Helan Prasad; Kuryan George (Current Medical Issues, 2022)
Background: Perinatal mortality rate (PMR) includes both fetal deaths and deaths occurring during the 1st week of life. Low birthweight (LBW) continues to be a significant problem with 14.6% of all births globally and 20% of all births in India being LBW. There is a powerful association between birthweight and perinatal mortality. This study looks at data from a rural block in South India to understand the trends, possible reasons, and strategies for interventions. Methodology: Information regarding 80,206 pregnancies who were registered in the community health and development (CHAD) program between January 1986 and December 2018 was obtained from the CHAD health information system. Trends regarding birthweight, gestational age, and perinatal mortality were extracted from this system and analyzed. Results: Among the 69,386 babies whose birthweights were recorded, 16.7% were LBW (<2.5 kg). The PMR has steadily declined from 45.2/1000 live births in the period 1986–1990 to 14.3/1000 live births during the period 2016–2018. The mean birthweight has shown a steady rise over the years from 2.73 kg in 1986–1990 to 2.9 in 2016–2018. The mean standard deviation height of the mother has gone up from 152.3 cm (5.4) between 1986–1990 and 156.3 cm (5.7) in the 2016–2018 period. The proportion of anemic women (hemoglobin <11 g/dL) in 1986–1990 was 46.4% and had drastically come down to 23.8% in 2016–2018. Conclusion: The decreasing PMR may be attributed to the increasing birthweight which may, in turn, be related to better nutritional status of mothers which is evident in the increased height and decreased proportion of anemic women.